2007
DOI: 10.1186/1476-4598-6-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of primary colorectal carcinomas, liver metastases, and carcinomatoses

Abstract: Background: Despite the fact that metastases are the leading cause of colorectal cancer deaths, little is known about the underlying molecular changes in these advanced disease stages. Few have studied the overall gene expression levels in metastases from colorectal carcinomas, and so far, none has investigated the peritoneal carcinomatoses by use of DNA microarrays. Therefore, the aim of the present study is to investigate and compare the gene expression patterns of primary carcinomas (n = 18), liver metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 67 publications
(63 reference statements)
0
42
1
1
Order By: Relevance
“…20, 21, 34, 52 Earlier, it was shown that SUB1 is amplified and over-expressed in the NSCLC cell lines, 53 invasive intraductal papillary mucinous neoplasm of the pancreas 54 and in carcinomatoses. 55 Additionally, it has been shown that exogenous overexpression of SUB1 could induce the transformation of a population of normal dermal multipotent fibroblasts to acquire malignant characteristics of anchorage-independent growth in vitro and tumorigenicity in nude mice. 56 Additionally, it was reported that SUB1 is upregulated in esophageal squamous cell carcinoma (ESCC) and its absence increased radiosensitivity of ESCC cells, and suppressed non-homologous end joining (NHEJ) activity via downregulation of XLF.…”
Section: Discussionmentioning
confidence: 99%
“…20, 21, 34, 52 Earlier, it was shown that SUB1 is amplified and over-expressed in the NSCLC cell lines, 53 invasive intraductal papillary mucinous neoplasm of the pancreas 54 and in carcinomatoses. 55 Additionally, it has been shown that exogenous overexpression of SUB1 could induce the transformation of a population of normal dermal multipotent fibroblasts to acquire malignant characteristics of anchorage-independent growth in vitro and tumorigenicity in nude mice. 56 Additionally, it was reported that SUB1 is upregulated in esophageal squamous cell carcinoma (ESCC) and its absence increased radiosensitivity of ESCC cells, and suppressed non-homologous end joining (NHEJ) activity via downregulation of XLF.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies used home-made cDNA microarrays [8], [13], one used the Agilent human 1A platform [9], and the last one used home-spotted chips using the Sigma human Oligolibrary [11]. Because these platforms did not use Affymetrix probes, we first converted our probe signature into a gene signature.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies presented gene signatures associated with metastatic disease containing more than 400 genes. Such long lists of genes are difficult to use for the development of new therapies [9], [10]. Among the five studies aimed at identifying the molecular mechanisms taking place during metastatic dissemination and growth, two did not succeed in the identification of a signature able to clearly separate primary cancers from metastatic tissues.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations